Analisis Pertanggungjawaban dan Perlindungan Pidana terhadap Pelaku dan Korban Tindak Pidana Eksibisionisme - Rafadhea Fauzia Aydraghifary; Rinaldy Amrullah; Sri Riski (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study examines criminal liability for the crime of exhibitionism in Indonesia and the forms of protection provided to its victims. Exhibitionism is a deviant behavior in the form of exposing genitals to others without consent, which is classified as a form of sexual harassment. Although often considered a minor act or even just "fun", exhibitionism has serious psychological impacts on victims, such as trauma, fear, anxiety, and long-term mental disorders, especially if it occurs repeatedly or is experienced by minors. From a legal aspect, the crime of exhibitionism can be prosecuted through several articles in the Criminal Code (KUHP), including Article 281 which regulates indecent acts in public, and Article 289 if the exhibitionism is carried out with violence or threats of violence. In addition, Law Number 44 of 2008 concerning Pornography can also be used as a legal basis, especially if the exhibitionism is carried out through digital media. If the victim is a child, Law Number 35 of 2014 concerning Child Protection will increase the perpetrator's punishment. The criminal liability of exhibitionists depends heavily on their mental state. Under Indonesian criminal law, a person can only be held criminally responsible if they are legally capable of being held accountable. If a perpetrator is proven to have a serious mental disorder based on a psychiatric expert's testimony, they may be subject to special measures instead of criminal punishment, such as rehabilitation in a mental hospital. Protection for victims of exhibitionism must be comprehensive. This includes facilitating the reporting process to authorities, prompt handling by law enforcement, providing counseling or psychological support, protecting the victim's identity, and educating the public to prevent exhibitionism. Integrating legal aspects, mental health, and public education is crucial in breaking the chain of this crime.